2014
DOI: 10.3855/jidc.3861
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial profile of Salmonella enterica serotype Choleraesuis from free-range swine in Kakamega fish market, western Kenya

Abstract: Introduction: Salmonella enterica subspecies enterica serovar Choleraesuis is a host-adapted, facultative, intracellular pathogen that causes swine paratyphoid. Its antimicrobial resistance presents a challenge to feed manufacturing industries. However, stopping antibiotics in animal feed would have economic implications for the industry. Methodology: Conventional microbial methods for isolation and identification of S. Choleraesuis were employed. The isolates were subjected to screening against 17 antimicrobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Moreover, cephalosporin-resistant isolates have frequently been detected in S . Choleraesuis and may therefore pose another threat to public health [ 32 , 41 , 42 ]. However, of the six cephalosporin antibiotics tested in our study, no cephalosporin-resistant isolates were detected.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cephalosporin-resistant isolates have frequently been detected in S . Choleraesuis and may therefore pose another threat to public health [ 32 , 41 , 42 ]. However, of the six cephalosporin antibiotics tested in our study, no cephalosporin-resistant isolates were detected.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Molino et al [43] revealed that S. Choleraesuis strain was resistant to two or more antibiotics. Onyango et al [44] found that S. Choleraesuis isolated from swine feces were sulfamethoxazole resistant. Different findings on antimicrobial susceptibility may be attributed to the genetic variability in these strains in different countries.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA of each strain was used as a template in PCR reactions to detect the presence of eight antibiotic resistance genes as previously described. These genes included ampC (Hanson et al, 1999), blaCTX (Moghaddam, Beidokhti, Jamehdar, & Ghahraman, 2014), blaTEM (Bert, Bramger, & Lambert-Zochovsky, 2002), blaZ (Olsen, Christensen, & Aarestrup, 2006), mecA (Duran, Ozer, Duran, Onlen, & Demir, 2012), oxa1 (Onyango, Ndeda, Wandili, Wawire, & Ochieng, 2014), oxa9 (Hanson et al, 1999), and shv (Fang, Ataker, Hedin, & Dornbusch, 2008).…”
Section: Detection Of Antibiotic Resistance Genes In Enterobacterial mentioning
confidence: 99%